2022
DOI: 10.48550/arxiv.2203.16842
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

X-ray emission of massive stars and their winds

Abstract: Most types of massive stars display X-ray emission that is strongly affected by the properties of their stellar winds. Single non-magnetic OB stars have an X-ray luminosity that scales with their bolometric luminosity and their emission is thought to arise from a distribution of wind-embedded shocks. The lack of significant short-term stochastic variability indicates that the winds consist of a large number of independent fragments. Detailed investigations of temporal variability unveiled a connection between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 171 publications
(292 reference statements)
0
4
0
Order By: Relevance
“…X-ray variables are highlighted (with "var") on the basis of Gaussian or Poissonian statistics, although inevitably these are limited to the brightest sources with unattenuated X-ray luminosities of 𝐿 X ≥ 10 33 erg s −1 . Oskinova (2005) concluded that, in general, binaries follow the canonical X-ray relationship for single early-type stars, although occasionally colliding wind systems exhibit enhanced, harder X-ray emission, with respect to single stars (Pittard 2011;Gagné et al 2012;Rauw 2022). In general, establishing the single or binary nature of early-type stars is notoriously difficult.…”
Section: T-rex Point Source Cataloguementioning
confidence: 99%
See 1 more Smart Citation
“…X-ray variables are highlighted (with "var") on the basis of Gaussian or Poissonian statistics, although inevitably these are limited to the brightest sources with unattenuated X-ray luminosities of 𝐿 X ≥ 10 33 erg s −1 . Oskinova (2005) concluded that, in general, binaries follow the canonical X-ray relationship for single early-type stars, although occasionally colliding wind systems exhibit enhanced, harder X-ray emission, with respect to single stars (Pittard 2011;Gagné et al 2012;Rauw 2022). In general, establishing the single or binary nature of early-type stars is notoriously difficult.…”
Section: T-rex Point Source Cataloguementioning
confidence: 99%
“…It is now established that a high fraction of massive stars lie in binary systems with short periods (Sana et al 2012). A subset of binaries are known to exhibit enhanced, often harder (few keV), Xray emission (Pollock 1987;Chlebowski & Garmany 1991;Rauw 2022) attributed to colliding stellar winds, although the majority of binaries do not exhibit excess X-ray emission (Oskinova 2005). Further, stellar atmosphere improvements to our understanding of massive stars have resulted in revisions to the properties of early-★ paul.crowther@sheffield.ac.uk type stars including their temperatures and luminosities (Crowther et al 2002b;Repolust et al 2004) and a subset of early-type stars are known to possess kG-scale magnetic fields (Grunhut et al 2017), so historical calibrations should be used with caution.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a non-thermal component in the X-ray spectra of 𝛾 Cas type stars remains an important problem. Rauw et al [11] believe that the X-ray spectrum of these stars is purely thermal, based on the results of Shrader et al [12]. These authors describe the X-ray spectrum of 𝛾 Cas itself in the region of 0.6-100 keV using the data from the Suzaku and Integral satellites and a thermal model with a temperature of 14 keV and with the addition of Gaussian profiles of the fluorescence…”
Section: Pos(muto2022)044mentioning
confidence: 99%
“…O vi λλ1031, 1037) N v λλ1238, 1242) are also sensitive to X-rays (e.g. Taresch et al 1997), which are known to originate in the winds of early-type stars (Rauw 2022). To date the majority of X-ray studies of OB stars have involved Milky Way stars, although deep Chandra X-ray observations of a few star-forming regions in the Magellanic Clouds have been obtained.…”
Section: Xshootumentioning
confidence: 99%